Identification of natural product 3, 5-diiodotyrosine as APOBEC3B inhibitor to prevent somatic mutation accumulation and cancer progression. Issue 11 (2nd November 2022) - Chen, Chunxia; Sui, Xinghua; Ning, Haoming; Sun, Yixuan; Du, Jiangfeng; Chen, Xiaotong; Zhou, Xiuman; Chen, Guanyu; Shen, Wenhui; Pang, Liwei; Zhou, Xiaowen; Shi, Ranran; et al.
Abstract : Background: The development of cancer is largely dependent on the accumulation of somatic mutations, indicating the potential to develop cancer chemoprevention agents targeting mutation drivers. However, ideal cancer chemoprevention agents that can effectively inhibit the mutation drivers have not been identified yet. Methods: The somatic mutation signatures and expression analyses of APOBEC3B were performed in patient with pan-cancer. The computer-aided screening and skeleton-based searching were performed to identify natural products that can inhibit the activity of APOBEC3B. 4-nitroquinoline-1-oxide (4-NQO)-induced spontaneous esophageal squamous cell carcinoma (ESCC) and azoxymethane/dextran sulfate sodium (AOM/DSS)-induced spontaneous colon cancer mouse models were conducted to investigate the influences of APOBEC3B inhibitor on the prevention of somatic mutation accumulation and cancer progression. Results: Here, we discovered that the cytidine deaminase APOBEC3B correlated somatic mutations were widely observed in a variety of cancers, and its overexpression indicated poor survival. SMC247 (3, 5-diiodotyrosine), as a source of kelp iodine without side effects, could strongly bind APOBEC3B (KD =65 nM) and effectively inhibit its deaminase activity (IC50 =1.69 µM). Interestingly, 3, 5-diiodotyrosine could significantly reduce the clusters of mutations, prevent the precancerous lesion progression, and prolong the survival in 4-NQO-induced spontaneous ESCC and AOM/DSS-induced spontaneous colon cancer mouse models. Furthermore, 3, 5-diiodotyrosine could reduce colitis, increase the proportion and function of T lymphocytes via IL-15 in tumor microenvironment. The synergistic cancer prevention effects were observed when 3, 5-diiodotyrosine combined with PD-1/PD-L1 blockade. Conclusions: This is the first prove-of-concept study to elucidate that the natural product 3, 5-diiodotyrosine could prevent somatic mutation accumulation and cancer progression through inhibiting the enzymatic activity of APOBEC3B. In addition, 3, 5-diiodotyrosine could reduce the colitis and increase the infiltration and function of T lymphocytes via IL-15 in tumor microenvironment. 3, 5-diiodotyrosine combined with PD-1/PD-L1 blockade could elicit synergistic cancer prevention effects, indicating a novel strategy for both prevent the somatic mutation accumulation and the immune-suppressive microenvironment exacerbation.